PENEMUAN PRIME MOVER INTEGRASI POTENSI PEMANGKU KEPENTINGAN PADA IMPLEMENTASI KONSERVASI SUMBER DAYA AIR (Studi Kasus: Keterpaduan Antarsektor di DAS Kawunganten) - Suhardi Alimudarto (Jurnal Sosioteknologi, 2009)
Global climate changes cause many environmental problems such as flood or even long dry season which bring suffer to the farmers. Because of that, various technique matters related to the Water Resources become one of the parts that face many challenges. Based on the research, there are 3 major motivators of integration potentials supporting the interests in the conservation of water resources: the role in developing community groups, the role of conservation community group of Water Resources, and the community based role.